THE PERFORMANCE OF WHITE GOLD CHICKEN WITH LANCY 6-14 WEEKS AGE GIVEN DRINKING WATER CONTAIN DRAGON FRUIT EXTRACT (Hylocereus polyrhizus) - N. M. A., Trisnayuni; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to determine the effect of the administration of dragon fruit skin extract (Hylocereus polyrhizus) on the performance of White Gold crosses with Lancy aged 6-14 weeks. This research was carried out on Cekomaria Street, Banjar Kedua, Peguyangan Kangin, Denpasar, Bali for 8 weeks. The design used was a Completely Randomized Design (CRD) with 4 treatments of Rations A, B, C, D and 5 replications and each replication consisted of 3 chickens of White Gold crossing with Lancy, a total of 60 chickens were used. The treatment given is, A: Without the administration of dragon fruit peel extract (Hylocereus polyrhizus), B: Addition of 5% dragon fruit skin extract (Hylocereus polyrhizus) given by drinking water, C: 10% addition of dragon fruit skin extract (Hylocereus polyrhizus ) given through drinking water and D: 15% addition of dragon fruit skin extract (Hylocereus polyrhizus) given by drinking water. Drinking water is given ad libitum and all treatments are given commercial feed with the same amount and nutrient content. The variables observed included initial body weight, final body weight, body weight gain, feed consumption, feed conversion ratio (FCR), drinking water consumption. The data obtained will be analyzed by analysis of variance, if there are significant differences (P <0.05), then followed by a multiple distance test from Duncan. The results showed that for each variable initial weight, final weight, weight gain, feed consumption ratio (FCR) in the treatment 0%, 5%, 10%, 15% were not significantly different (P> 0.05), while in treatment water consumption variables 5%, 10%, 15% significantly different (P <0.05) than controls. Based on the results of the study it can be concluded that the administration of dragon fruit skin extract (Hylocereus polyrhizus) through drinking water did not affect initial body weight, final body weight, body weight gain, feed consumption, feed convertion ratio (FCR) in White Gold crosses with Lancy age 6 -14 weeks, but it affects the consumption of drinking water.   Keywords : Performance, crossbred chicken, dragon fruit skin (hylocereus polyrhizus).